The Effectiveness of Online Learning on the Level of Understanding of International Course Material - Mohzana, Mohzana; Murcahyanto, Hary; Haritani, Hartini (Sumber Belajar Sejahtera, 2024)
This research aims to evaluate the effectiveness of online learning in achieving educational goals through understanding the material of international course subjects. A descriptive qualitative approach was employed, involving 87 students as research participants. Data collection techniques included questionnaires, interviews, and tests to measure students' understanding of international course materials. The results indicate that online learning effectiveness was rated as good based on an average questionnaire score of 55.25. Meanwhile, test results showed that 50.57% of students had a good understanding of the material, while 48.27% were below the proficient level. Thus, online learning is considered effective in enhancing understanding of international course materials. These findings highlight the importance of integrating technology in the learning process to achieve educational goals effectively.